2017
DOI: 10.5380/rsa.v17i3.44630
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da eficiência agronômica da inoculação com AzzoFix® (Azospirillum brasilense, estirpes: Abv5 e Abv6) sobre a cultura do milho

Abstract: Resumo -Com o objetivo de avaliar a eficiência agronômica da inoculação com Azospirillum sp.sobre a cultura do milho (Zea mays L.) foram conduzidos experimentos nas cidades de Ponta Grossa e Palmeira -PR, na safra de 2013/2014. O delineamento experimental foi em blocos ao acaso, com oito tratamentos e quatro repetições. Os tratamentos consistiram em: 1-Testemunha; 2-50% da dose de nitrogênio (N) recomendada para a cultura e inoculação das sementes com AzoTotal (150 mL 25 kg -1 de sementes); 3-Dose de N recomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The results showed a significant interaction between copper doses and sources of inocula for wheat productivity, being greater with the inoculation of A. brasilense at zero dose of copper in the soil (Figure 1A). A. brasillense performs the function of biologically fixing nitrogen and increasing the absorption surface of plant roots and volume of the exploited soil (Repke et al, 2013;Milléo & Cristófolli, 2016). Tiller emission of wheat plants is also higher when inoculated with A. brasilense, as demonstrated in the present work (Table 2), and this increase is considered a mechanism of promotion in yield in response to inoculation (Fukami et al, 2016).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The results showed a significant interaction between copper doses and sources of inocula for wheat productivity, being greater with the inoculation of A. brasilense at zero dose of copper in the soil (Figure 1A). A. brasillense performs the function of biologically fixing nitrogen and increasing the absorption surface of plant roots and volume of the exploited soil (Repke et al, 2013;Milléo & Cristófolli, 2016). Tiller emission of wheat plants is also higher when inoculated with A. brasilense, as demonstrated in the present work (Table 2), and this increase is considered a mechanism of promotion in yield in response to inoculation (Fukami et al, 2016).…”
Section: Resultssupporting
confidence: 71%
“…The inoculation of bacteria of the genus Azospirillum has been studied as an alternative to reduce costs with wheat fertilization due to the potential of fixing N 2 (Numoto et al, 2019;Medeiros et al, 2007). However, these bacteria can also promote hormonal changes and induce greater root growth and consequently greater absorption of water and nutrients (Bashan & Bashan, 2005), denominated plant growth promoter bacteria (Milléo & Cristófolli, 2016). Several studies demonstrate the ability of different genera of bacteria to grow in soils with high concentrations of metals (Uzel & Ozdemir, 2009;Chen et al, 2008;Florentino et al, 2009), thus being an alternative for wheat cultivation in soils contaminated with copper.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using this bacterium makes nitrogen available through biological fixation (Pedrinho et al 2010;Dartora et al 2013) and biocontrol of plant pathogens. These factors directly enhance root growth, thus increasing crop productivity (Milléo and Cristófoli 2016;Cadore et al 2016). A study by Dartora et al (2016) and Di Salvo et al (2018) found that combining nitrogen fertilizer and seed inoculation with microorganisms increased maize growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…The use of plant growth-promoting Rhizobacteria (PGPR) can be an alternative for growing sorghum in soil contaminated with copper. Among the species of microorganisms, the bacterium Azospirillum brasilense has been recommended by many researchers (Araújo et al, 2014;Hungria et al, 2016), as, in addition to its ability to fix N 2 , it also promotes plant growth through the synthesis of phytohormones and compounds such as auxin, cytokinin, gibberellin, abscisic acid, ethylene, and salicylic acid (Pedraza, 2008), which increase the growth and absorption surface of plant roots and, consequently, the volume of soil explored (Milléo and Cristófoli, 2016). Furthermore, it helps mitigate abiotic stresses, such as salinity and drought, and mitigates the effects of excessive compounds and heavy metals (Fukami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%